RAKUT SITELU AS A BRAND OF RELIGIOUS MODERATION MEDIA IN NORTH SUMATRA - Hasan Sazali; Abdul Rahman Matondang; Bakhrul Khair Amal (UIN Antasari Banjarmasin, 2023)
The purpose of this research is to analyze the existing Rakut Sitelu system in the social life of the Karo ethnic group in North Sumatra and to synthesize the values of Rakut Sitelu as a means of religious moderation in North Sumatra. The method used in this research is ethnography and reference tracing, involving data collection from interviews, books, journals, and manuscripts for further analysis. The results of this research conclude that Rakut Sitelu has deep roots in the Karo ethnic kinship, where the three bonds of kalimbubu, senina, and anak beru coexist in daily activities with an attitude of mutual respect, assistance, and cooperation based on their respective structures, without distinguishing religion. Rakut Sitelu also exhibits manifestations of religious moderation values, such as high tolerance, anti-violence, and accommodation of their own culture. This can serve as a reference for implementing moderate values in North Sumatra, especially for the Karo ethnic group.